Some Common Fixed Point Results for Modified Subcompatible Maps and Related Invariant Approximation Results. (14th July 2014) - Rathee, Savita; Kumar, Anil
Abstract : We improve the class of subcompatible self-maps used by (Akbar and Khan, 2009) by introducing a new class of noncommuting self-maps called modified subcompatible self-maps. For this new class, we establish some common fixed point results and obtain several invariant approximation results as applications. In support of the proved results, we also furnish some illustrative examples.